Knockout of SlALKBH2 weakens the DNA damage repair ability of tomato - Tan, Tingting; Li, Yangyang; Tang, Boyan; Chen, Yating; Chen, Xinru; Xie, Qiaoli; Hu, Zongli; Chen, Guoping (Plant science (Limerick), 2022)
During the growth and evolution of plants, genomic DNA is subject to constant assault from endogenous and environmental DNA damage compounds, which will result in mutagenic or genotoxic covalent adducts. Whether for prokaryotes, eukaryotes or even viruses, maintaining genome integrity is critical for the continuation of life. Escherichia coli and mammals have evolved the AlkB family of Fe(II)/alpha-ketoglutarate-dependent dioxygenases that repair DNA alkylation damage. We identified a functional homologue with EsAlkB and HsALKBH2 in tomatoes, and named it SlALKBH2. In our study, the SlALKBH2 knockout mutant showed hypersensitivity to the DNA mutagen MMS and displayed more severe growth abnormalities than wild-type plants under mutagen treatment, such as slow growth, leaf deformation and early senescence. Additionally, genes with high transcriptional activity, such as rDNA, have increased methylation under MMS treatment. In conclusion, this study shows that the tomato SlALKBH2 gene may play an important role in ensuring the integrity of the genome. •Knockout of SlALKBH2 weakens the DNA damage repair ability of tomato.•The repair pathway of this gene is different in animals and tomatoes.•It was found for the first time that this gene was related to rDNA demethylation in the presence of exogenous methylating agents.•Knockout of SlALKBH2 will lead to insufficient DNA repair under exogenous pressure, and then lead to leaf senescence and death.